Contesting performance : global sites of research - McKenzie, Jon; Roms, Heike; Wee, C. J. Wan-ling (Performance interventions, 2012)
"Contesting Performance is a unique and dynamic collection of essays by leading international scholars that addresses the global development of cultural performance research. The volume functions as a critical reader on diverse, localised approaches to studying performance, using case studies from Mexico, Australia, Japan, Israel and Croatia, amongst others. Featuring contributors such as Freddie Rokem, Shannon Jackson, Lauren Kruger and Sharon Aronson-Lehavi, this landmark collection will also reveal networks of practical and theoretical concerns that contest dominant models of performance studies"--Provided by publisher.